Pore structure of wastewater sludge chars and their water retention impacts in different soils. (June 2021) - Turunen, Mika; Hyväluoma, Jari; Keskinen, Riikka; Kaseva, Janne; Nikama, Johanna; Reunamo, Aino; Rasa, Kimmo
Abstract : Feasibility of pyrolysing wastewater sludge for char and energy production is dependent on the usability of the produced sludge char. This study aimed to produce mechanistic information of char impacts on amended porous media by determining (1) pore structure of sludge chars with 3D image analyses and (2) their influence on water retention and shrinkage properties of three contrasting soils. The pore structure of the chars consisted of crevices and large spheres. Their water retention impacts were minor, even though the low-porous char slightly increased porosity in the amended materials in various pore-size ranges. The dominating, though small, impacts were the increase in easily drainable interpores and decrease in smallest pore sizes relevant for plant available water. The char impacts were more visible in fine-than coarse-textured soils. The chars also significantly reduced shrinkage in clay soils. The results were insensitive to sludge feedstock or char particle size. Highlights: 3D imaging showed how sludge char pore space consisted of crevices and large spheres. Dominating pore sizes were ≤50 μm, but their water retention impacts were minor. Mechanistic analysis showed how interpore impacts on porosity dominated. The char water retention impacts were clearer in fine-than coarse-textured media. Variability in production process and particle size had a low impact on the results.